Negative thermal expansion material KxMgxLu2-xW3O12 as well as preparation method and application thereof
By preparing KxMgxLu2-xW3O12 negative thermal expansion material, the existing materials have solved the problems of small thermal expansion coefficient and narrow temperature zone, and the application in industrial production is realized, and a wide bandgap semiconductor solution is provided for integrated circuits and chip manufacturing.
Patent Information
- Application Number
- CN202411387102.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
The thermal expansion coefficient of existing negative thermal expansion materials is not small enough and the temperature zone is narrow, which limits its widespread use in industrial applications, especially the complex synthesis process under high pressure/high temperature or oxygen-free conditions, and low-frequency phonon-driven NTE materials The synthesis conditions are simple but the element position substitution is poor.
Prepare a negative thermal expansion material KxMgxLu2-xW3O12, and obtain products with negative thermal expansion properties by selecting K2CO3, MgO, Lu2O3 and WO3 as raw materials, mixing according to a specific molar ratio and pre-sintering and secondary sintering treatment. .
The materials with a negative thermal expansion coefficient in the range of -7.61×10-6 ~ -10.6×10-6 K-1 have good thermal stability and low cost, suitable for industrial production, suitable for biomedical, aerospace and In the fields of precision instruments, it can also be used as wide-bandgap semiconductors for integrated circuits and chip manufacturing.
Smart Images

Figure CN119191841A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal expansion materials, and specifically relates to a negative thermal expansion material K x Mg x Lu 2-x W3O 12 And its preparation method and application. Background Art
[0002] Most materials show positive thermal expansion due to non-harmonic potential energy, while a few materials show the characteristic of "heat shrinkage and cold expansion" when the temperature changes, that is, negative thermal expansion, due to their special crystal structure. Negative thermal expansion materials can effectively alleviate the damage to material properties caused by drastic temperature changes and can be used in many fields, such as: aerospace materials, integrated circuit boards, engine components and optical devices. In 1845, Guillaume discovered Invar alloy (Fe 0.65 Ni 0.35 ), its thermal expansion coefficient decreases significantly near the Curie point, showing the characteristics of near-zero expansion, so it is widely used in the field of precision instruments. However, due to the problems of the thermal expansion coefficient of the discovered negative thermal expansion materials being not small enough and the negative thermal expansion temperature range being narrow, the application value of these materials is not high, so they have not received widespread attention. In 1996, the Sleight team discovered that ZrW2O8 has excellent NTE performance in an ultra-wide temperature range of 0.3~1050K, and subsequently discovered A2M3O 12 series of NTE materials, so NTE materials have been rapidly developed. Today, NTE compounds can be roughly divided into two types according to the mechanism classification: phonon-driven and electron-driven. Phonon-driven includes the transverse vibration of bridging oxygen atoms, RUMs, etc. The negative thermal expansion of many oxides, cyanides, and fluorides can be explained by phonon-driven; the other type of NTE phenomenon driven by electrons usually appears together with other physical properties. For example, in PbTiO3, the weakening of its spontaneous polarization is accompanied by a decrease in the displacement of ions in the compound, which ultimately manifests itself macroscopically as the lattice shrinking along the direction where polarization is likely to occur, resulting in negative thermal expansion; LaCu3Fe4O 12 When the temperature rises from 100K to 400K, although it shows positive thermal expansion, at 400K, the unit cell volume drops sharply due to the charge transfer of metal ions in the compound, resulting in overall volume shrinkage. However, such materials need to be synthesized under extreme conditions such as high pressure / high temperature or oxygen-free, which greatly limits their application in industry. However, the synthesis conditions of some low-frequency phonon-driven NTE materials are relatively simple, and the positions of different elements can be replaced, so they have been studied more deeply. For example, A2M3O 12 type of material, the A position can be Sc 3+ It can also be replaced by Zr 4+Mg 2+ At the same time, the M position can be Mo 6+ or W 6+ Each synthesized substance has different applications, such as Sc2Mo3O 12 Can be used in everything from white light emitting diodes to thermal shock resistant components; Cr2Mo3O 12 It has low thermal expansion performance. In addition, phonon-driven NTE materials have a wider operating NTE temperature range, such as TaVO5 between 293~873K, ZrV2O7 between 375~873K, and even more so, such as Sc2Mo3O 12 , a-ZrW2O8, the temperature range reaches above 1000K. The volume thermal expansion coefficient (CTE) of the frame structure NTE material is mainly distributed in the range of 0 to -60×10 -6 K -1 Between, such as Lu2W3O 12 The CTE at 473~1073K is -18.5×10 -6 K -1 ScF3 has a CTE of -42×10 -6 K -1 .
[0003] NZP materials refer to a class of materials with a similar structure to NaZr2(PO4)3. This series of materials has a wide negative thermal expansion temperature range, is not prone to phase change, has strong ion substitution, high ion conductivity, and is radiation resistant. Therefore, it has great application potential. Most of the important properties of this type of structural material come from its unique crystal structure. It has a hexagonal phase structure and belongs to the R-3c space group. Taking NaZr2(PO4)3 as an example, PO4 tetrahedrons and ZrO6 octahedrons are connected by sharing oxygen atoms to construct a three-dimensional framework structure. Na + Located in the gaps of the framework structure. The versatility of NZP materials lies in the flexible substitution of metal ions: Na + It can be replaced by Li, K, 1 / 2Ca, 1 / 2Sr, 1 / 2Ba ions; Zr can be replaced by Hf, Ti, Al+Na, Fe+Na, Cr+Na, etc.; and P can be replaced by As and Si+Na. Therefore, the required properties can be customized by changing the composition and proportion. For example, in Ba 1+x Zn4P 6-2x Si 2x O 24 In this series, as the amount of Si substitution increases, the body thermal expansion of the material in this system gradually changes from negative to positive, and this system shows zero expansion in a wide range; 1+x Zn4P 6-2x Si 2x O24 In this system, the thermal expansion of the composition remains almost stable with the change of Si content, which reflects the difference between the compositions of Ba and Sr, two different substitution elements, and can be adjusted in the control and formulation of the anisotropy of NZP. Therefore, the thermal expansion performance can be regulated by substitution of different metal ions and different proportions, and thermal expansion materials with specific functions can be designed. Summary of the invention
[0004] The present invention aims to provide a negative thermal expansion material K x Mg x Lu 2-x W3O 12 And its preparation method and application.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A negative thermal expansion material with the molecular formula K x Mg x Lu 2-x W3O 12 , where 0.4≤x≤0.8.
[0006] A method for preparing a negative thermal expansion material: selecting K2CO3, MgO, Lu2O3 and WO3 as raw materials, and preparing the material according to the molar ratio of K2CO3:MgO:Lu2O3:WO3=( x / 2): x ∶(1- x / 2):3 weigh and grind and mix evenly, directly sinter the obtained mixed powder or sinter it after tableting, the sintering temperature is 900~1200℃, the time is 6~24h, and it is cooled to room temperature to obtain the target product K x Mg x Lu 2-x W3O 12 .
[0007] Preferably, K2CO3, MgO, Lu2O3 and WO3 are weighed in proportion and ground and mixed evenly, and the obtained mixed powder is first pre-sintered directly or pre-sintered after tableting, and then the pre-sintered product is ground and mixed evenly, and then sintered again after tableting; the pre-sintering temperature is 500~800℃ and the time is 6~24h, and the secondary sintering temperature is 900~1200℃ and the time is 6~24h.
[0008] Preferably, K2CO3, MgO, Lu2O3 and WO3 are weighed in proportion and ground and mixed uniformly, and wet grinding is adopted. Ethanol is added during grinding, and the added amount is based on wetting K2CO3, MgO, Lu2O3 and WO3.
[0009] Preferably, dry grinding is used when grinding and mixing the pre-sintered product uniformly.
[0010] Preferably, the purity of K2CO3, MgO, Lu2O3 and WO3 is 99~99.99wt%.
[0011] Preferably, all sintering processes are carried out at a heating rate of 5-10°C / min to reach the sintering temperature.
[0012] Preferably, all the tablets involved are pressed into round tablets with a diameter of 8 to 10 mm and a height of 3 to 6 mm.
[0013] Preferably, for all tableting processes involved, a pressure of 2 to 10 MPa is applied to the mold and maintained for 2 to 5 minutes.
[0014] A negative thermal expansion material is used as a semiconductor in the field of integrated circuit or chip manufacturing.
[0015] Beneficial effect: The present invention proposes for the first time a x Mg x Lu 2-x W3O 12 Negative thermal expansion materials, where 0.4≤ x ≤0.8, and the phase purity characterization and thermal expansion properties were studied. The XRD characterization results showed that when 0.4≤ x When ≤0.6, the synthesized samples are all pure phase. x =0.7 and 0.8, only a small amount of impurity MgWO4 appears; thermal expansion results show that this series of samples has negative thermal expansion performance, and the negative thermal expansion coefficient covers -7.61×10 -6 ~ -10.6×10 -6 K -1 , has good thermal stability, simple preparation process, low cost, suitable for industrial production, and is expected to be applied in high-tech fields such as biomedical materials, aerospace equipment, and precision instruments; In addition, the present invention K x Mg x Lu 2-x W3O 12 It can be used as a wide bandgap semiconductor and applied in the fields of integrated circuit and chip manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 :The present invention K x Mg x Lu 2-x W3O 12 ( x =0.4, 0.5, 0.6, 0.7, 0.8) samples at room temperature.
[0017] Figure 2 :The present invention K 0.4 Mg 0.4 Lu 1.6 W3O 12 Retiveld refinement pattern of room temperature XRD of the sample.
[0018] Figure 3 :The present invention K 0.5 Mg 0.5 Lu 1.5 W3O 12 Retiveld refinement pattern of room temperature XRD of the sample.
[0019] Figure 4 :The present invention K 0.6 Mg 0.6 Lu 1.4 W3O 12 Retiveld refinement pattern of room temperature XRD of the sample.
[0020] Figure 5 :The present invention K 0.7 Mg 0.7 Lu 1.3 W3O 12 Retiveld refinement pattern of room temperature XRD of the sample.
[0021] Figure 6 :The present invention K 0.8 Mg 0.8 Lu 1.2 W3O 12 Retiveld refinement pattern of room temperature XRD of the sample.
[0022] Figure 7 :The present invention K 0.4 Mg 0.4 Lu 1.6 W3O 12 Thermogravimetric curve of the in-situ weight loss test of the sample.
[0023] Figure 8 :The present invention K x Mg x Lu 2-x W3O 12 ( x =0.4, 0.5, 0.6, 0.7, 0.8) The curve of the relative length of the sample changing with temperature.
[0024] Fig. 9 :The present invention K 0.4 Mg 0.4 Lu 1.6 W3O 12 UV absorption spectra of samples. DETAILED DESCRIPTION
[0025] The following is a clear and complete description of the technical solution of the present invention in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A negative thermal expansion material with the molecular formula K 0.4 Mg 0.4 Lu 1.6 W3O 12 , the preparation steps are as follows: (1) Select analytical grade K2CO3, MgO, Lu2O3 and WO3 as raw materials, weigh them according to the molar ratio of K2CO3:MgO:Lu2O3:WO3=0.2:0.4:0.8:3, put them into an agate mortar and grind them continuously, and add an appropriate amount of anhydrous ethanol (the amount added is based on wetting K2CO3, MgO, Lu2O3 and WO3) to accelerate the grinding until the mixture is evenly mixed. Transfer the mixed powder obtained after grinding into a crucible, and put it into a muffle furnace and heat it to 600℃ at a heating rate of 5℃ / min. Keep it warm and pre-sinter for 6h. After the pre-sintering is completed, cool it naturally to room temperature and then take it out; (2) The mixed powder obtained by pre-sintering in step (1) was again placed in an agate mortar for dry grinding and uniformly ground. The powder was pressed into a disc with a diameter of 8 mm and a height of 3 mm by a tablet press at a pressure of 10 MPa for 2 min. The disc was placed in a muffle furnace and heated to 1100°C at a heating rate of 5°C / min. The mixture was kept at this temperature for a second sintering for 10 h. After the sintering was completed, the mixture was naturally cooled to room temperature in the furnace and then taken out to obtain the final product K. 0.4 Mg 0.4 Lu 1.6 W3O 12 .
[0028] Example 2
[0029] A negative thermal expansion material with the molecular formula K 0.5 Mg 0.5 Lu 1.5 W3O 12 , the preparation steps are as follows: (1) Select analytical grade K2CO3, MgO, Lu2O3 and WO3 as raw materials, weigh them according to the molar ratio of K2CO3:MgO:Lu2O3:WO3=0.25:0.5:0.75:3, put them into an agate mortar and grind them continuously, and add an appropriate amount of anhydrous ethanol (the amount added is based on wetting K2CO3, MgO, Lu2O3 and WO3) to accelerate the grinding until the mixture is uniformly mixed, transfer the mixed powder obtained after grinding into a crucible, and put it into a muffle furnace and heat it to 600℃ at a heating rate of 5℃ / min, and keep it warm for pre-sintering for 6h. After the pre-sintering is completed, naturally cool it to room temperature with the furnace and then take it out; (2) The mixed powder obtained by pre-sintering in step (1) was again placed in an agate mortar for dry grinding and uniformly ground. The powder was pressed into a disc with a diameter of 8 mm and a height of 3 mm by a tablet press at a pressure of 10 MPa for 2 min. The disc was placed in a muffle furnace and heated to 1100°C at a heating rate of 5°C / min. The mixture was kept at this temperature for a second sintering for 10 h. After the sintering was completed, the mixture was naturally cooled to room temperature in the furnace and then taken out to obtain the final product K. 0.5 Mg 0.5 Lu 1.5 W3O 12 .
[0030] Example 3
[0031] A negative thermal expansion material with the molecular formula K 0.6 Mg 0.6 Lu 1.4 W3O 12 , the preparation steps are as follows: (1) Select analytical grade K2CO3, MgO, Lu2O3 and WO3 as raw materials, weigh them according to the molar ratio of K2CO3:MgO:Lu2O3:WO3=0.3:0.6:0.7:3, put them into an agate mortar and grind them continuously, and add an appropriate amount of anhydrous ethanol (the amount added is based on wetting K2CO3, MgO, Lu2O3 and WO3) to accelerate the grinding until the mixture is uniformly mixed, transfer the mixed powder obtained after grinding into a crucible, and put it into a muffle furnace and heat it to 600℃ at a heating rate of 5℃ / min, and keep it warm for pre-sintering for 6h. After the pre-sintering is completed, naturally cool it to room temperature with the furnace and then take it out; (2) The mixed powder obtained by pre-sintering in step (1) was again placed in an agate mortar for dry grinding and uniformly ground. The powder was pressed into a disc with a diameter of 8 mm and a height of 3 mm by a tablet press at a pressure of 10 MPa for 2 min. The disc was placed in a muffle furnace and heated to 1100°C at a heating rate of 5°C / min. The mixture was kept at this temperature for a second sintering for 10 h. After the sintering was completed, the mixture was naturally cooled to room temperature in the furnace and then taken out to obtain the final product K. 0.6 Mg 0.6 Lu 1.4 W3O 12 .
[0032] Example 4
[0033] A negative thermal expansion material with the molecular formula K 0.7 Mg 0.7 Lu 1.3 W3O 12 , the preparation steps are as follows: (1) Select analytical grade K2CO3, MgO, Lu2O3 and WO3 as raw materials, weigh them according to the molar ratio of K2CO3:MgO:Lu2O3:WO3=0.35:0.7:0.65:3, put them into an agate mortar and grind them continuously, and add an appropriate amount of anhydrous ethanol (the amount added is based on wetting K2CO3, MgO, Lu2O3 and WO3) to accelerate the grinding until the mixture is evenly mixed. Transfer the mixed powder obtained after grinding into a crucible, and put it into a muffle furnace and heat it to 600℃ at a heating rate of 5℃ / min. Pre-sinter it for 6h. After the pre-sintering is completed, cool it naturally to room temperature and then take it out; (2) The mixed powder obtained by pre-sintering in step (1) was again placed in an agate mortar for dry grinding and uniformly ground. The powder was pressed into a disc with a diameter of 8 mm and a height of 3 mm by a tablet press at a pressure of 10 MPa for 2 min. The disc was placed in a muffle furnace and heated to 1100°C at a heating rate of 5°C / min. The mixture was kept at this temperature for a second sintering for 10 h. After the sintering was completed, the mixture was naturally cooled to room temperature in the furnace and then taken out to obtain the final product K. 0.7 Mg 0.7 Lu 1.3 W3O 12 .
[0034] Example 5
[0035] A negative thermal expansion material with the molecular formula K 0.8 Mg 0.8 Lu 1.2 W3O 12 , the preparation steps are as follows: (1) Select analytical grade K2CO3, MgO, Lu2O3 and WO3 as raw materials, weigh them according to the molar ratio of K2CO3:MgO:Lu2O3:WO3=0.4:0.8:0.6:3, put them into an agate mortar and grind them continuously, and add an appropriate amount of anhydrous ethanol (the amount added is based on wetting K2CO3, MgO, Lu2O3 and WO3) to accelerate the grinding until the mixture is evenly mixed. Transfer the mixed powder obtained after grinding into a crucible, and put it into a muffle furnace and heat it to 600℃ at a heating rate of 5℃ / min. Pre-sinter it for 6h. After the pre-sintering is completed, cool it naturally to room temperature and then take it out; (2) The mixed powder obtained by pre-sintering in step (1) was again placed in an agate mortar for dry grinding and uniformly ground. The powder was pressed into a disc with a diameter of 8 mm and a height of 3 mm by a tablet press at a pressure of 10 MPa for 2 min. The disc was placed in a muffle furnace and heated to 1100°C at a heating rate of 5°C / min. The mixture was kept at this temperature for a second sintering for 10 h. After the sintering was completed, the mixture was naturally cooled to room temperature in the furnace and then taken out to obtain the final product K. 0.8 Mg 0.8 Lu 1.2 W3O 12 .
[0036] Product characterization and related performance testing K prepared in Example 1-5 x Mg x Lu 2-x W3O 12 ( x =0.4, 0.5, 0.6, 0.7, 0.8) samples at room temperature XRD patterns are shown in Figure 1 K prepared in Example 1-5 x Mg x Lu 2-x W3O 12 ( x = 0.4, 0.5, 0.6, 0.7, 0.8) samples' room temperature XRD Retiveld refinement patterns are shown in Figure 2-6 . Figure 2-4 The single-phase refined spectrum shown shows that the refined peaks fit well with the experimental peaks, indicating that the synthesized sample is pure phase. x = 0.7, 0.8 samples were subjected to dual-phase refinement (impurity phase MgWO4), and the refined peaks matched well with the experimental peaks, indicating that the impurity phase was MgWO4.
[0037] K prepared in Example 1 0.4 Mg 0.4 Lu 1.6 W3O 12 The thermogravimetric curve of the in-situ weight loss test is as follows Figure 7 As shown. Figure 7 It can be seen that the curve decreases at around 0~100℃, with a reduction rate of only 2.6%, and then remains almost unchanged, indicating that the sample has low water absorption and good stability in a wide temperature range.
[0038] K prepared in Example 1-5 x Mg x Lu 2-x W3O 12 ( x =0.4, 0.5, 0.6, 0.7, 0.8) with temperature. Figure 8It can be seen that the synthesized sample first exhibits a strong positive expansion before 125°C, and then a sharp decrease in volume occurs. Figure 7 It can be concluded that the presence of water molecules affects the thermal expansion properties of Examples 1-5. x As the K increases, the drastic change of the curve is alleviated, indicating that the water content of the sample decreases. Then, all proportions of samples begin to show linear negative expansion. 0.4 Mg 0.4 Lu 1.6 W3O 12 The thermal expansion coefficient is: -10.2×10 -6 K -1 (141~400℃); K 0.5 Mg 0.5 Lu 1.5 W3O 12 The thermal expansion coefficient is: -10.6×10 -6 K -1 (135~400℃); K 0.6 Mg 0.6 Lu 1.6 W3O 12 The thermal expansion coefficient is: -9.25×10 -6 K -1 (137~400℃); K 0.7 Mg 0.7 Lu 1.3 W3O 12 The thermal expansion coefficient is: -7.61×10 -6 K -1 (127~400℃); K 0.8 Mg 0.8 Lu 1.2 W3O 12 The thermal expansion coefficient is: -9.15×10 -6 K -1 (137~400℃). The results show that: x Mg x Lu 2-x W3O 12 ( x =0.4, 0.5, 0.6, 0.7, 0.8) products achieve the regulation of the thermal expansion coefficient of the product by doping the two elements in different proportions.
[0039] K prepared in Example 1 0.4 Mg 0.4 Lu 1.6 W3O 12 The UV spectrum of the sample is shown in Fig. 9 .Depend on Fig. 9It can be seen that the sample has an absorption peak in the ultraviolet wavelength region. According to the formula proposed by Kubelka and Munk: E g =1240 / λ g The band gap of the sample was obtained to be 3.76 eV, indicating that the sample is a wide-bandgap semiconductor and is expected to be used in the fields of integrated circuit and chip manufacturing.
Claims
1. A negative thermal expansion material, characterized in that: Its molecular formula K x Mg x Lu 2-x W3O 12 , where 0.4≤x≤0.
8.
2. A method for preparing a negative thermal expansion material as claimed in claim 1, characterized in that: Select K2CO3, MgO, Lu2O3 and WO3 as raw materials, according to the molar ratio of K2CO3:MgO:Lu2O3:WO3=( x / 2): x ∶(1- x / 2):3 weigh and grind and mix evenly, directly sinter the obtained mixed powder or sinter it after tableting, the sintering temperature is 900~1200℃, the time is 6~24h, and it is cooled to room temperature to obtain the target product K x Mg x Lu 2-x W3O 12 .
3. The method for preparing a negative thermal expansion material according to claim 2, characterized in that: After K2CO3, MgO, Lu2O3 and WO3 are weighed in proportion and ground and mixed evenly, the obtained mixed powder is first pre-sintered directly or pre-sintered after tableting, and then the pre-sintered product is ground and mixed evenly, and then tableted and re-sintered; the pre-sintering temperature is 500~800℃ and the time is 6~24h, and the secondary sintering temperature is 900~1200℃ and the time is 6~24h.
4. The method for preparing a negative thermal expansion material according to claim 2 or 3, characterized in that: When K2CO3, MgO, Lu2O3 and WO3 are weighed in proportion and ground and mixed evenly, wet grinding is adopted. Ethanol is added during grinding, and the added amount is based on wetting K2CO3, MgO, Lu2O3 and WO3.
5. The method for preparing a negative thermal expansion material according to claim 3, characterized in that: When the pre-sintered product is ground and mixed uniformly, dry grinding is adopted.
6. The method for preparing a negative thermal expansion material according to claim 2 or 3, characterized in that: The purity of K2CO3, MgO, Lu2O3 and WO3 is 99~99.99wt%.
7. The method for preparing a negative thermal expansion material according to claim 2 or 3, characterized in that: For all sintering processes involved, the temperature was raised to the sintering temperature at a heating rate of 5 to 10 °C / min.
8. The method for preparing a negative thermal expansion material according to claim 2 or 3, characterized in that: All tablets involved are pressed into round tablets with a diameter of 8~10mm and a height of 3~6mm.
9. The method for preparing a negative thermal expansion material according to claim 2 or 3, characterized in that: For all tablet pressing involved, a pressure of 2~10MPa is applied to the mold and the pressure is maintained for 2~5min.
10. Use of the negative thermal expansion material as claimed in claim 1 as a semiconductor in the field of integrated circuit or chip manufacturing.
Citation Information
Patent Citations
Preparation method for Cu-based composite material based on negative thermal expansion particles
CN104775045A
Novel negative thermal expansion ceramic Zr2W2P2O15 and sintering synthetic method therefor
CN105272199A
Negative thermal expansion material Sc2W4O15 and solid-phase sintering synthesis method thereof
CN106478099A
Anti-ferroelectric single crystal material, preparation method and application thereof
CN109778316A
Negative thermal expansion material ABC (MoO4) 3 and preparation method thereof
CN118026677A
